Kualitas Layanan Nsw Berdasarkan Persepsi Dan Harapan Pengguna Layanan Di Pelabuhan Tanjung Priok - Puriningsih, Feronika Sekar; Chairunnisa, Chairunnisa (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
The importance of the port services is ideal for supporting the economy has become a commonexpectations. Bureaucratic, widespread practice extortion everywhere, the flow of importedgoods and so on, resulting in economic conditions, Indonesia suffered. An effort toreduce costly economy is removing barriers in the smooth flow of exports and imports ofgoods, from production to sale. VVhen processing services are still done manually, there arestill many obstacles to the free flow of goods, so the demand for goods and services, whichintegrates Harbour. National single window